1999
DOI: 10.1097/00005792-199909000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Initial and Recurrent Thromboembolic Disease Among Patients with Malignancy Versus Those without Malignancy: Risk Analysis Using Medicare Claims Data

Abstract: Although the association between malignancy and thromboembolic disease is well established, the relative risk of developing initial and recurrent deep vein thrombosis (DVT) or pulmonary embolism (PE) among patients with malignancy versus those without malignancy has not been clearly defined. The Medicare Provider Analysis and Review Record (MEDPAR) database was used for this analysis. Patients hospitalized during 1988-1990 with DVT/PE alone, DVT/PE and malignancy, malignancy alone, or 1 of several nonmalignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
536
4
34

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 840 publications
(599 citation statements)
references
References 38 publications
25
536
4
34
Order By: Relevance
“…[1][2][3][4][5][6] However, the risk of VTE among cancer patients differs considerably 3,5 and is below 10% even in certain groups of patients with advanced cancer. 7 Predictive parameters are, therefore, required to stratify patients into risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, the risk of VTE among cancer patients differs considerably 3,5 and is below 10% even in certain groups of patients with advanced cancer. 7 Predictive parameters are, therefore, required to stratify patients into risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of thrombosis is high in adenocarcinomas such as ovarian, prostate and gastro-intestinal carcinoma [2,3], but is particularly high (up to 57%) in patients with pancreatic cancer [4][5][6]. However, the cause of this association is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…According to data from Medicare International Classification of Disease, 9th Revision (ICD-9) hospital discharge diagnoses between 1988 and 1990 in the United States, ovarian cancer exhibited the highest incidence of cancer-related VTE, at 120 out of 10 000 patients (Levitan et al, 1999). Moreover, some reports have suggested that clear cell carcinoma of the ovary is particularly likely to develop VTE (Pather and Quinn, 2005).…”
mentioning
confidence: 99%